Exploratory factor analysis of entrepreneurial behaviour among business owners in food processing industry - Jamaluddin, Askiah; Paim, Laily; Redzuan, Ma'rof; Abdul Rahim @ Abdul Wahab, Husniyah (Secholian Publication, 2017)
The purpose of this paper is to identify the key domains of entrepreneurial behaviour among business owner in food processing industry. The study utilized a deductive research design and quantitative method. There are twenty-one statements about entrepreneurial behaviour to discover a core action associated with entrepreneurial behaviour. An entrepreneurial behaviour is defined as small family business strategic behaviour that captures specific entrepreneurial aspects (Walker and Brown, 2004). In additions, it is the actions taken by the small business owner to achieve business performance (Delmar, 1996). According to Kirkley (2015), entrepreneurial behaviour as self determined human action is based on a specific set of values which the individual uses to make decisions about how to behave in situations that a meaningful to their business. The questionnaires focused primarily on the meaning of entrepreneurial behaviour as self-determination to be succeed in business. There were 70 respondents were selected by simple random sampling. The data were analysed by Exploratory Factor Analysis (EFA) and categorised into relevant domains. The result shows four specific domains of entrepreneurial behaviour business owner in food processing industry, namely, leadership, pro- activeness, committed and risk taking. The finding items to each of these domains are consistent with the small family business perspective. The practical implication is the presence of the specific core action associated with entrepreneurial behaviour. The business owner should employ the four core action to sustain the business. The result of this study is importance to academician in small business area, business advisor from government and non government sectors, and small family business owner.